Legal Certainty of Indonesia's Nickel Downstream Policy Due to the European Union's Lawsuit at the WTO - Christwan Christwan; Ahmad Saleh Kusnowibowo (Jurnal Indonesia Sosial Sains, 2024)
Indonesia's nickel downstreaming policy, which prohibits the export of nickel ore with a grade of <1.7%, aims to increase added value and support national development. However, the European Union views this policy as a violation of the General Agreement on Tariffs and Trade (GATT) 1994, leading to a lawsuit at the World Trade Organization (WTO) in 2021. This research employs a normative-descriptive method to analyze the dispute settlement process at the WTO, the impacts of the downstreaming policy for Indonesia, and its prospects for legal certainty in the future. The findings indicate that Indonesia lost at the panel level because the policy was deemed inconsistent with Article XI:1 of the GATT, although an appeal was filed in 2022. Despite legal and diplomatic challenges, downstreaming remains a key strategy to enhance Indonesia's economy. In conclusion, this policy must be refined through strengthening domestic industrial capacity and harmonizing regulations with international standards.